Introduction to ecotoxicology (Blackwell Science, 1999)
Provides an invaluable overview of the subject for students taking courses in ecotoxicology and environmental pollution, as well as wider degree programmes in biology, ecology, wildlife management, environmental science, sanitation engineering and related subjects. Softcover. DLC: Pollution--Environmental aspects